Pola Konsumsi Sayur Buah Dan Status Gizi Remaja Putri Di SMP Negeri 1 Bangli - Widyaswari, Ni Made Jenita; Widarti, DCN, M.Kes, I Gusti Agung Ari; Dewantari, SKM, M.For, Ni Made (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
The results of the 2018 Riskesdas in Bali Province were that 96.5% of the population still did not consume enough vegetables and fruit. This research aims to determine the consumption patterns of fruit and vegetables and the nutritional status of female students at SMP Negeri 1 Bangli. This type of observational research with a cross sectional design, a population of 40 female students was randomly selected. implemented in April 2024. Data was collected using a questionnaire and the SQ-FFQ Form. The results of this study were that some of the samples, namely 67.5% had normal nutritional status, 10.0% had less nutritional status, 10.0% had more nutritional status, 12.5% were obese. The sample's daily consumption pattern of vegetables and fruit is in the sufficient category, namely 55.0% vegetables and 65.0% fruit. The sample consuming vegetables was still in the deficient category with an obese nutritional status of 60.0% and the frequency of vegetable consumption with an obese nutritional status of 66.0% was in the deficient category. Meanwhile, fruit consumption with poor nutritional status is 75.0% in terms of type, quantity and frequency of fruit consumption. It is recommended that female students with normal nutritional status maintain vegetable and fruit consumption patterns, while female students with malnutrition, overnutrition and obesity can pay attention to their vegetable and fruit consumption patterns in order to achieve good nutritional status. Schools are advised to sell snacks made from vegetables and fruit.